A future resistance breeding strategy against Varroa destructor in a small population of the dark honey bee. Issue 5 (20th October 2019) - Guichard, Matthieu; Neuditschko, Markus; Fried, Padruot; Soland, Gabriele; Dainat, Benjamin
Abstract : In scientific literature, host resistance of Apis mellifera against its parasite Varroa destructor is often presented as a potential solution to enable a sustainable relationship between both species and secure pollination and beekeeping services. Surprisingly, there are only few studies investigating the interest of beekeepers for this topic. In this paper, we propose a method to assess the desirability of resistance as part of a breeding goal, with a particular focus on small closed populations. The Swiss population of Apis mellifera mellifera is taken as case study. The general importance of this selection objective as well as the variability of the acceptance of beekeepers are studied. Thereafter, the willingness to pay for resistance is assessed to highlight possible compromises beekeepers could accept between different qualities they expect from their honey bees. Finally, the main characteristics of the breeding program desired by the beekeepers are presented. In our example, beekeepers are generally in favour of resistant honey bees even if differences in the expected breeding goals were identified. The majority is interested in a breeding strategy to select for resistant stock even though honey bees would produce less honey, swarm more often or be less gentle, showing a clear desirability for resistant traits. Furthermore, we noticed that beekeepers prefer locally selected honey bees displaying a broad genetic diversity. The presented method can be easily applied to evaluate the acceptance of new breeding objectives and to assess the potential of future strategies focusing on resistance against V. destructor in breeding programs involving beekeepers and research institutes.